AB0805 Low Grade Systemic Inflammation is Associated with Low Ultrasound Velocity in Older Men, A Population Based Study (LASA). (10th June 2014) - Den Uyl, D.; van Schoor, N.M.; Braveboer, N.; Lips, P.; Lems, W.F.
Abstract : Background: Elevated systemic levels of pro-inflammatory cytokines are likely involved in the pathogenesis of osteoporosis in healty individuals. Objectives: To investigate whether low grade inflammation was associated with bone markers, bone quality, bone mass and fracture risk in a population of older persons. Methods: Serum interleukin 6 (IL-6), high-sensitivity C-reactive protein (hsCRP) and erythrocyte sedimentation rate (ESR) were measured in 1287 participants of the Longitudinal Aging Study Amsterdam (LASA), a population based study with healthy older men and women (age 76 (±6.7) years). Bone quality was measured by quantitative ultrasound measurements (QUS) at baseline and after 3 years at the calcaneus and bone mass was measured by dual-energy x-ray absorptiometry (DXA) at the spine and hips in a subpopulation. Furthermore, the bone markers osteocalcin (OC) and urinary excretion of deoxypyridinoline (DPD) were determined Incident fractures were recorded during 6 years of follow-up. IL-6 was dichotomized at the detection limit (5 pg/ml) because of the high number of participants (76%) with levels below the detection limit. hsCRP was categorized into 3 groups based on clinical relevant concentrations: <3, 3-10, >10 μg/ml. ESR was classified in tertiles (≤7, 8-16, 17-90). Multivariable linear regression analyses were used to evaluate the cross-sectional relation between inflammatory markers and bone mass and bone turnover. The longitudinal association of inflammatory markers and bone loss was evaluated by multivariable linear regression analyses with delta BMD as dependent variable and the association of inflammatory markers with time to fracture by Cox proportional hazard analyses. All multivariable analyses included adjustments for potential confounders. Results: Multivariable regression analyses revealed that slightly elevated hsCRP plasma levels (3-10 μg/ml) were associated with low bone mineral density in the femoral neck in men (β= -0.126; 95%CI -0.07- -0.001, p<0.05). After excluding participants with inflammatory diseases this was no longer significant. Increased IL-6 and ESR levels were associated with quantitative ultrasound measurements in healthy men (β=-0.98; 95%CI -57.72- -6.42, p<0.05) and women (β= -0.221; 95%CI -15.39- -3.27, p<0.05) respectively. No significant associations were found between inflammatory markers with bone markers, bone loss at the spine or hips, fracture rate or time to fracture. Conclusions: Elevated inflammatory markers are associated with low quantitative ultrasound measurements, suggesting an impaired bone quality in healthy older men. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4641